Area Classification and Types of Protection for Explosive Atmospheres: A Review - Bhagirath Ahirwal; A. K. Singh; R. K. Vishwakarma (Institute of Advanced Engineering and Science, 2015)
Explosionproof (Ex) equipment is vital for use in explosive atmospheres. The knowledge of basic of area classification, zone, temperature class, types of protection and source of ignition is mandatory for testing, manufacturing, use, installation, inspection and maintenance of Ex equipment. The paper describes the area classification, types of protection and equipment protection level for hazardous areas.